Deciphering the fungal symphony: unveiling the fungal dynamics during the fermentation of traditional Chinese strong-flavor Daqu - Zhao, Lina; Zhang, Wenjing; Niu, Yuting; Chen, Xiaohan; Guo, Jiuyang; Wu, Ying; Li, Xuan; Gu, Shaobin (Frontiers in Microbiology, 2025)
Daqu, a starter culture rich in microorganisms like bacteria and fungi, is central to vinification and liquor brewing, yet fungal contributions are often understudied. In this study, we used Illumina MiSeq sequencing to investigate the succession of fungal community during Chinese strong-flavor liquor fermentation. The results showed that the alpha and beta diversity of fungal community were significantly different during Daqu fermentation. The dominant phyla and genera are Ascomycota and Saccharomycopsis, respectively. Co-occurrence network analysis identified 10 keystone species during Daqu fermentation, displaying that the positive correlations (99.64%) dominated the fungal network. The redundancy analysis showed that moisture has the most significant influence on the Daqu fungal community. Concurrently, a robust association was observed between 10 keystone fungal genera and environmental parameters such as acidity and moisture. These findings not only elucidated the intricate dynamics of the fungal community succession and the interplays among fungi but also pinpointed the primary drivers of the fungal community and its keystone species during the Daqu fermentation process. Ultimately, this research presented novel perspectives for enhancing the quality and precision of liquor production by shedding light on the central role of keystone species in maintaining community stability and their adaptive responses to environmental stimuli.